Corporalidade neopentecostal: análise e concepção de corpo na Igreja Bola de Neve de Marília, SP - Cesarino, Flavia Tortul [UNESP] (2015)
A few years ago the number of evangelicals in the country has grown remarkably, especially when it comes to neopentecostal churches. The Bola de Neve Church fits this type of designation and is relatively new. Since the beginning facing young people, this institution has shown tremendous growth in a short time. Considering it as a social phenomenon, this work is dedicated to investigate an important aspect observed in the same: the body, specifically analyze and interpret the body techniques and the design of the body present in the Bola de Neve Church of Marilia, SP. Importantly, the body is not searched only in times of spiritual contact, but the idea is to interpret various aspects related to the body (beauty, sexuality, religious meaning, relationship with culture, sacred and profane, among others). However, when it comes to body part in contact of the faithful with the Holy Spirit, for example, this type of religious experience can trigger some phenomena, such as speaking in tongues (glossolalia), which occurs during prayers, worship time, among others. As this happens, physical manifestations elapses, that is, there is an often repeated sign repertoire, but also includes the search expressions neopentecostal individual body generally as a way to be specific. In examining this corporeality (the gestural behavior of the faithful in general), you must describe it to understand the function of these physical manifestations, that is, because they are empirical phenomena, know what role do they play in the interaction of the individual with the sacred, that meaning is assigned to them by the faithful and by the institution and because they are new meanings. Is this what you want to understand through the development of an ethnography done through a participant observation in the Bola de Neve Church of Marilia, SP, and observation of classroom cults and cults of that church on internet (recorded on his mother, located in São Paulo), ally...